Neural substrates of self‐ and external‐preoccupation: A voxel‐based morphometry study - Ikeda, Shigeyuki (Brain Behav, 2019)
INTRODUCTION: Self‐ and external‐preoccupation have been linked to psychopathological states. The neural substrates underlying self‐ and external‐preoccupation remain unclear. In the present study, we aim to provide insight into the information‐processing mechanisms associated with self‐ and external‐preoccupation at the structural level. METHODS: To investigate the neural substrates of self‐ and external‐preoccupation, we acquired high‐resolution T1‐weighted structural images and Preoccupation Scale scores from 1,122 young subjects. Associations between regional gray matter volume (rGMV) and Preoccupation Scale subscores for self‐ and external‐preoccupation were estimated using voxel‐based morphometry. RESULTS: Significant positive associations between self‐preoccupation and rGMV were observed in widespread brain areas such as the bilateral precuneus and posterior cingulate gyri, structures known to be associated with self‐triggered self‐reference during rest. Significant negative associations between external‐preoccupation and rGMV were observed only in the bilateral cerebellum, regions known to be associated with behavioral addiction, sustained attention, and reward system. CONCLUSION: Our results reveal distinct neural substrates for self‐ and external‐preoccupation at the structural level.